EVALUATING THE COOLING EFFECT AND THERMAL COMFORT OF SMALL URBAN GREEN SPACES ON THE CITY PEOPLE: THE CASE OF PLANNED RESIDENTIAL AREA OF UTTARA, DHAKA - Jhumur, Saniya Tabassum (International Journal of Research -GRANTHAALAYAH, 2021)
Urban Green spaces explore innovative approaches to increase the quality of urban settings, enhance livability and promote sustainable lifestyles. They provide environmental benefits through their effects on negating urban heat, increase comfort and the cooling impact of surrounding area. Therefore, it is very important to understand the mechanisms by which these benefits accrue. There is, thus, a need for proper planning of urban greenery to increase the benefits sought with the needs of the community and the functionality that the urban green space will serve. In Dhaka the overall situation of urban greenery and Park greenery is in a very poor state. In this research three small parks in the planned residential area of Uttara have been selected to find out their cooling effect and the level of comfort they exert on community people. Simulation studies were also done, to check the environmental performances of the Parks and on their surroundings. The analysis identifies that these Parks have an impact, the intensity of which depends on the type and quality of its vegetation, its design parameters, connectivity and of course on surrounding urban morphology. Thus, the paper offers a planning for urban park design for planned areas of Dhaka city.